Sprint interval training on constant work rate high intensity exercise: time to task failure, biomolecular glycolytic pathway and neuromuscular function adaptations. - Poli, Rodrigo de Araujo Bonetti de (2024)
The present thesis has been divided into two independent studies. The first study aimed to examine the impact of a 5-week sprint interval training (SIT) on glycolytic response (i.e., glycolytic enzyme content and activity, and glycogen content) and its relationship with time to task failure (TTF) during constant load exercise (CWR) performed above critical intensity. METHODS: In this study, 14 physically active men were randomized into the SIT group (SITG; n=8; 3 times a week, 4-6 efforts of 30-second Wingate) over 5 weeks, and a control group (n=6). Initially, participants underwent: i) an incremental ramp test to measure cardiorespiratory function; ii) CWR cycling at 150% of power output associated with the respiratory compensation point (RCP-PO) with muscle biopsies at rest and immediately after task failure. After 5 weeks, the same assessments were repeated. Glycogen phosphorylase (GPhos), hexokinase (HK), phosphofructokinase (PFK), lactate dehydrogenase (LDH) enzyme content and activities, as well as glycogen content, were analyzed. RESULTS: Content and activity of GPhos, HK, PFK, LDH enzymes, as well as glycogen content, improved post-training only in SITG; however, no difference in glycogen utilization was observed between groups or over time. Additionally, no difference in TTF was observed when CWR was adjusted to post-training physical condition. The second study aimed to investigate whether 5 weeks of SIT could improve neuromuscular function [NMF; maximal voluntary isometric contraction (iMVC) + peripheral nerve stimulation (PNS) with evoked force assessment and electromyography (EMG)] and TTF during CWR performed above critical intensity. METHODS: 21 physically active men participated in the study, randomly allocated to SITG (n=11) and control group (n=10). The experimental design was similar to the first study; however, instead of muscle biopsy, iMVC + PNS + EMG were performed to verify neuromuscular function. RESULTS: SIT did not induce changes in NMF measured by iMVC, as well as in fatigue and EMG signal during CWR. No significant changes in TTF corresponding to the current 150% of RCP-PO were observed. However, SITG showed a significant improvement over time in training outcomes (dynamic neuromuscular function; maximum power and peak power). THESIS CONCLUSION: 5 Weeks of SIT were effective in causing changes in the analyzed glycolytic variables and dynamic neuromuscular function; however, these changes do not seem to underpin the maintenance of exercise tolerance during severe-intensity efforts.